Phytoremediation of heavy metal contaminated groundwater using tropical wetland plants: Lepironia articulata and typha angustifolia - Jiang, Baiyang; Noor Hijrah, Sa'adon; Doh, Shu Ing; Suryati, Sulaiman; Abdul Syukor, Abd Razak (Penerbit UMP, 2025)
This study examines the efficacy of Lepironia articulata and Typha angustifolia in horizontal subsurface flow constructed wetlands (HSSF-CWs) for removing organic pollutants and heavy metals from contaminated water over a 10-week monitoring period. For Lepironia articulata, the average COD, BOD5, Pb, Zn, Fe, and Cu concentrations were 38.2 mg/L, 13.09 mg/L, 0.0416 mg/L, 0.0368 mg/L, 1.1539 mg/L, and 0.0096 mg/L, with corresponding removal efficiencies of 31.02%, 22.89%, 11.18%, 19.87%, 23.18%, and 22.53%, respectively. For Typha angustifolia, they were 50.7 mg/L, 11.43 mg/L, 0.0289 mg/L, 0.0163 mg/L, 0.9795 mg/L, and 0.0095 mg/L, with removal efficiencies of 8.24%, 38.34%, 37.16%, 57.41%, 32.83%, and 34.08%, respectively. FESEM-EDX imaging revealed distinct accumulation patterns, as Lepironia articulata tended to sequester more metals in its leaves, whereas Typha angustifolia retained a greater proportion in the stem. These findings highlight the complementary strengths of both macrophytes in mitigating organic and metal contaminants through wetland-based treatment.